Artificial functional aggregate curing agent, artificial functional aggregate and preparation method

Through artificial functional aggregate curing agent and hydrothermal reaction technology, the problems of waste soil resource utilization and high-quality fire-free functional aggregate preparation are solved, and efficient resource utilization of waste soil and functional aggregate production with excellent performance are achieved, simplifying The process flow and reduce energy consumption.

CN119320252AInactive Publication Date: 2025-01-17JIANGSU JICUI FUNCTIONAL MATERIALS RES INST CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411881831.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as complex process, high energy consumption and low product cylinder pressure strength in large-scale resource utilization of slag and preparation of high-quality sinter-free functional aggregates.

Method used

Using artificial functional aggregate curing agents, including dispersants, stimulators, enhancers, active agents and polymerizers, the ratio of accelerators to be combined with slags is prepared by combining and defining the ratio of accelerators to produce slags Soil, gelled materials and siliceous solid waste are used in a resource-based manner through hydrothermal reactions.

Benefits of technology

It realizes large-scale resource utilization of slag, and produces high-quality functional aggregates with excellent performance, improves the cylinder pressure strength and hydrothermal reaction speed of the product, simplifies the process flow, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an artificial functional aggregate curing agent, an artificial functional aggregate and a preparation method. The curing agent comprises 20-80 parts of a dispersing agent, 5-40 parts of an exciting agent, 5-40 parts of a reinforcing agent, 1-30 parts of an activating agent, 1-5 parts of an accelerant and 1-20 parts of a polymerizing agent. The weight ratio of the accelerant to the polymerizing agent is 1: (2-20). Under the combined action of an exciting agent, a reinforcing agent and an activating agent in the curing agent, the activity of the muck is fully excited, clay components in the muck are further destroyed, bound water in the muck is removed, silicate minerals in the muck are released, the activity in the muck is further released, on one hand, the siliceous activity in the muck is supplemented, hydrothermal products are increased, and therefore the product performance is improved; on the other hand, seed crystals are provided for rear-end hydrothermal synthesis through the accelerant and the polymerizing agent, the hydrothermal reaction speed can be increased, product crystals can be rapidly formed at the initial stage of the reaction, and therefore the performance of the functional aggregate is effectively improved, and the unfired functional aggregate product with the excellent performance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to an artificial functional aggregate curing agent, an artificial functional aggregate and a preparation method. Background Art

[0002] Patent CN114716255A proposes a shield slag firing functional aggregate improver and a shield slag sintering functional aggregate method. The improver is made of urea formaldehyde resin, calcium carbonate, calcium sulfate, and bentonite, and then the improver is added to the shield soil and stirred to form improved slag, which is then made into raw material balls and fired to obtain functional aggregate. The firing process requires preheating, controlling the heating rate, and firing at a high temperature of 1150°C to obtain functional aggregate products. The process is relatively complicated and energy consumption is high, which is not conducive to large-scale resource production.

[0003] Patent CN113860843B proposes a non-fired functional aggregate and its preparation method, using sludge as the main raw material, first mixed with thickener, expanded perlite, short fiber, water repellent, curing agent, and binder to obtain component A; then the water retaining agent and expanded perlite particles are mixed and stirred evenly to obtain component B, and component A and component B are mixed and put into a ball forming machine to obtain non-fired functional aggregate. The process is relatively complicated, and the reagent components need to be used in different categories. The cylinder pressure strength of the final product functional aggregate is low, and the actual application scenarios are limited.

[0004] How to realize large-scale resource utilization of slag and prepare high-performance non-fired functional aggregate products is still a technical problem that needs to be solved urgently. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings, one of the purposes of the present invention is to provide an artificial functional aggregate curing agent, which can be made into high-quality functional aggregate products and realize the resource utilization of slag.

[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is: an artificial functional aggregate curing agent, including: 20-80 parts of dispersant, 5-40 parts of activator, 5-40 parts of reinforcing agent, 1-30 parts of active agent, 1-5 parts of promoter, and 1-20 parts of polymerizer.

[0007] Exemplarily, the dispersant is in a range of 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts or any two of them; the activator is in a range of 5 parts, 10 parts, 20 parts, 30 parts, 40 parts or any two of them; the enhancer is in a range of 5 parts, 10 parts, 20 parts, 30 parts, 40 parts or any two of them; the activator is in a range of 1 part, 10 parts, 20 parts, 30 parts or any two of them; the promoter is in a range of 1 part, 2 parts, 3 parts, 4 parts, 5 parts or any two of them; the polymerizer is in a range of 1 part, 5 parts, 10 parts, 15 parts, 20 parts or any two of them.

[0008] Preferably, the curing agent includes: 25-75 parts of dispersant, 10-30 parts of activator, 5-15 parts of reinforcing agent, 5-15 parts of activator, 0.5-3 parts of accelerator, and 5-14 parts of polymerizing agent.

[0009] Further, the weight ratio of the accelerator to the polymerizer is 1:2-20. Exemplarily, the weight ratio of the accelerator to the polymerizer is 1:2, 1:4, 1:5, 1:6, 1:8, 1:10, 1:12, 1:14, 1:15, 1:16, 1:18, 1:20 or a range consisting of any two thereof.

[0010] Preferably, the weight ratio of the accelerator to the polymerizer is 1:4-10.

[0011] Furthermore, the dispersant is selected from at least one of fly ash, stone powder, kiln dust, slag, concrete powder and waste lime.

[0012] Preferably, the dispersant is selected from at least one of fly ash and waste lime.

[0013] Furthermore, the particle size of the fly ash is 100-600 mesh.

[0014] Preferably, the particle size of fly ash is 200-325 mesh.

[0015] Furthermore, the activator is selected from at least one of cement clinker, sodium sulfate, calcium sulfate and potassium sulfate.

[0016] Furthermore, the enhancer is selected from at least one of sodium chloride, calcium chloride and potassium chloride.

[0017] Furthermore, the active agent is selected from at least one of calcium hydroxide, sodium hydroxide, potassium hydroxide and calcium oxide.

[0018] Furthermore, the accelerator is selected from at least one of calcium carbonate, tobermorite, and hydrated calcium silicate.

[0019] Preferably, the accelerator is selected from at least one of tobermorite and hydrated calcium silicate.

[0020] Furthermore, the polymerizing agent is selected from at least one of polyvinyl alcohol, water glass, epoxy resin, and organic silica gel binder.

[0021] Preferably, the polymerizing agent is selected from at least one of water glass and polyvinyl alcohol. Furthermore, the preparation method of the artificial functional aggregate curing agent is: after mixing the dispersant, stimulant, reinforcing agent, activating agent, accelerator and polymerizing agent, grinding them to a particle size of ≤0.075 mm.

[0022] An artificial functional aggregate comprises 55-70% of slag, 20-40% of cementitious material, 10-25% of siliceous solid waste and the above-mentioned curing agent.

[0023] Furthermore, the curing agent accounts for 1-10% of the total weight of the slag, cementitious materials and siliceous solid waste.

[0024] Preferably, the curing agent accounts for 2-6% of the total weight of the slag, cementitious materials and siliceous solid waste.

[0025] Furthermore, the slag is selected from one or more of engineering slag, building slag, shield slag, underground slag and sawdust.

[0026] Furthermore, the cementitious material is selected from one or more of silicate cement, slag cement, carbide slag, quicklime, gypsum, and waste lime.

[0027] Furthermore, the siliceous solid waste is selected from one or more of fly ash, quartz tailings, stone powder, and concrete powder.

[0028] A method for preparing an artificial functional aggregate comprises the following steps: S1, mixing slag, cementitious material, siliceous solid waste and the above-mentioned curing agent to prepare a mixture; S2, the mixture is granulated using a granulating device to obtain a functional aggregate green body; S3. The functional aggregate green body is subjected to hydrothermal reaction to obtain artificial functional aggregate.

[0029] Furthermore, in step S2, the granulation equipment is a double-roll granulation equipment, a disc granulation equipment or an extrusion granulation equipment.

[0030] Furthermore, in step S3, the hydrothermal temperature of the hydrothermal reaction is 150-200° C., the hydrothermal pressure is 0.48-1.6 MPa, and the hydrothermal time is 4-12 h.

[0031] The beneficial effects of the present invention are: 1) The present application obtains a curing agent by compounding a dispersant, an activator, an enhancer, an active agent, a promoter, and a polymerizer, and limiting the ratio of the promoter to the polymerizer; wherein the activator, the enhancer, and the active agent work together to fully stimulate the activity of the slag, further destroy the clay components inside the slag, remove the bound water inside the slag, and release the internal silicate minerals; the promoter and the polymerizer can provide seeds for subsequent reactions and accelerate the reaction rate; the dispersant helps to evenly disperse the raw materials; the curing agent is used for the preparation of artificial functional aggregates, and can obtain excellent performance non-fired functional aggregate products, thereby realizing large-scale resource utilization of slag.

[0032] 2) The curing agent combined with the cementitious material can effectively improve the active composition of the mixture and further release the internal activity of the slag. On the one hand, it can supplement the silica activity inside the slag and increase the hydrothermal products, thereby improving the product performance. On the other hand, it can provide seeds for the back-end hydrothermal synthesis through promoters and polymerizers, which can accelerate the hydrothermal reaction rate and quickly form product crystals in the early stage of the reaction, thereby effectively improving the performance of functional aggregates.

[0033] 3) This application uses slag as the main raw material, combined with slag curing agent, cementitious materials, siliceous solid waste, and combined with hydrothermal technology to produce high-quality functional aggregate products, realize the resource utilization of slag, and propose a feasible technical path and technical solution for the disposal of slag. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0035] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0036] A method for preparing an artificial functional aggregate comprises the following steps: S1. Mix the slag, cementitious materials, siliceous solid waste and curing agent to obtain a mixture.

[0037] In some embodiments, the curing agent includes: 20-80 parts of a dispersant, 5-40 parts of an activator, 5-40 parts of a reinforcing agent, 1-30 parts of an active agent, 1-5 parts of a promoter, and 1-20 parts of a polymerizing agent.

[0038] In some embodiments, the curing agent includes: 25-75 parts of dispersant, 10-30 parts of activator, 5-15 parts of reinforcing agent, 5-15 parts of activator, 0.5-3 parts of accelerator, and 5-14 parts of polymerizing agent.

[0039] In some embodiments, the weight ratio of the accelerator to the polymerizing agent is 1:2-20.

[0040] In some embodiments, the weight ratio of the accelerator to the polymerizing agent is 1:4-10.

[0041] In some embodiments, the dispersant is selected from at least one of fly ash, stone powder, kiln dust, slag, concrete powder, and waste lime.

[0042] In some embodiments, the dispersant is selected from at least one of fly ash and waste lime.

[0043] In some embodiments, the fly ash has a particle size of 100-600 mesh.

[0044] In some embodiments, the fly ash has a particle size of 200-325 mesh.

[0045] In some embodiments, the activator is selected from at least one of cement clinker, sodium sulfate, calcium sulfate, and potassium sulfate.

[0046] In some embodiments, the enhancer is selected from at least one of sodium chloride, calcium chloride, and potassium chloride.

[0047] In some embodiments, the active agent is selected from at least one of calcium hydroxide, sodium hydroxide, potassium hydroxide, and calcium oxide.

[0048] In some embodiments, the accelerator is selected from at least one of calcium carbonate, tobermorite, and hydrated calcium silicate.

[0049] In some embodiments, the accelerator is selected from at least one of tobermorite and hydrated calcium silicate.

[0050] In some embodiments, the polymerizing agent is selected from at least one of polyvinyl alcohol, water glass, epoxy resin, and organic silica gel binder.

[0051] In some embodiments, the polymerizing agent is selected from at least one of water glass and polyvinyl alcohol.

[0052] The preparation method of the artificial functional aggregate curing agent is as follows: after mixing the dispersant, the stimulator, the reinforcing agent, the activating agent, the accelerator and the polymerizing agent, the mixture is ground to a particle size of ≤0.075 mm.

[0053] In some embodiments, the curing agent accounts for 1-10% of the total weight of the slag, siliceous solid waste, and cementitious material.

[0054] In some embodiments, the curing agent accounts for 2-6% of the total weight of the slag, siliceous solid waste, and cementitious materials.

[0055] In some embodiments, the slag is selected from one or more of engineering slag, building slag, shield slag, and underground slag.

[0056] In some embodiments, the cementitious material is selected from one or more of Portland cement, slag cement, carbide slag, quicklime, gypsum, and waste lime.

[0057] In some embodiments, the siliceous solid waste is selected from one or more of fly ash, quartz tailings, stone powder, and concrete powder.

[0058] In some embodiments, the slag accounts for 40-70% of the total weight of the artificial functional aggregate raw materials, the cementitious material accounts for 15-40% of the total weight of the artificial functional aggregate raw materials, and the siliceous solid waste accounts for 10-25% of the total weight of the artificial functional aggregate raw materials.

[0059] S2. The mixed material is granulated using a granulating device to obtain a functional aggregate green body.

[0060] In some embodiments, the granulation device is a roller granulation device, a disk granulation device or an extrusion granulation device for granulation.

[0061] S3. The green functional aggregate is sent into a hydrothermal reactor, and water vapor is introduced to perform a hydrothermal reaction. After the reaction is completed, the green functional aggregate is obtained without curing.

[0062] In some embodiments, the hydrothermal temperature of the hydrothermal reaction is 150-200° C., the hydrothermal pressure is 0.48-1.6 MPa, and the hydrothermal time is 4-12 h.

[0063] Example The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0064] Preparation Example Component tests were conducted on the selected slag, siliceous solid waste and cementitious materials, and the test results are shown in Tables 1-3.

[0065] The slag is engineering slag with a moisture content of 21.5%. Through XRF analysis, its chemical composition and weight percentage are shown in Table 1.

[0066] Table 1 Main element composition of construction waste soil

[0067] Siliceous solid waste is stone powder from a stone processing plant. Through XRF analysis, its chemical composition and weight percentage are shown in Table 2.

[0068] Table 2 Main element composition of stone powder

[0069] The silicate cement from the building material yard was selected as the cementitious material. Through XRF analysis, its chemical composition and weight percentage are shown in Table 3: Table 3 Main element composition of silicate cement

[0070] Example 1 An artificial functional aggregate, the preparation method of which is as follows: S1. Mix slag (60 parts of construction slag), cementitious material (15 parts of silicate cement), siliceous solid waste (25 parts of stone powder) and curing agent (4 parts) to prepare a mixture, wherein the curing agent accounts for 4% of the total mass of slag, cementitious material and siliceous solid waste.

[0071] The curing agent is prepared by weight, and the raw materials include: 50 parts of dispersant, 20 parts of activator, 10 parts of enhancer, 10 parts of activator, 1.3 parts of promoter, and 9.7 parts of polymerizer, wherein the mass ratio of promoter to polymerizer is 1:7.5.

[0072] The dispersant is fly ash with a particle size of 325 meshes; the activator is sodium sulfate; the enhancer is sodium chloride; the active agent is sodium hydroxide; the promoter is tobermorite; and the polymerizer is water glass.

[0073] The curing agent is prepared by the following method: the dispersant, the stimulator, the reinforcing agent, the activating agent, the accelerator and the polymerizing agent are mixed and then ground to an average particle size of less than 0.075 mm.

[0074] S2. The mixed material is granulated using a disc granulating device to obtain a functional aggregate green body.

[0075] S3. The green functional aggregate is fed into a hydrothermal kettle, and steam is introduced into the kettle for hydrothermal reaction. The temperature of the hydrothermal reaction is 185°C, the hydrothermal time is 6 hours, and the hydrothermal pressure is 1.1 MPa. After the hydrothermal reaction is completed, the finished functional aggregate is obtained.

[0076] Example 2 An artificial functional aggregate, the preparation method of which is as follows: S1. Mix slag (60 parts of construction slag), cementitious material (15 parts of silicate cement), siliceous solid waste (25 parts of stone powder) and curing agent (2 parts) to prepare a mixture, wherein the curing agent accounts for 2% of the total mass of slag, cementitious material and siliceous solid waste.

[0077] The curing agent is prepared by weight, and the raw materials include: 25 parts of dispersant, 10 parts of activator, 5 parts of enhancer, 5 parts of activator, 0.5 parts of promoter, and 5 parts of polymerizer, wherein the mass ratio of promoter to polymerizer is 1:10.

[0078] The dispersant is fly ash with a particle size of 325 meshes; the activator is sodium sulfate; the enhancer is sodium chloride; the active agent is sodium hydroxide; the promoter is tobermorite; and the polymerizer is water glass.

[0079] The curing agent is prepared by the following method: the dispersant, the stimulator, the reinforcing agent, the activating agent, the accelerator and the polymerizing agent are mixed and then ground to an average particle size of less than 0.075 mm.

[0080] S2. The mixed material is granulated using a disc granulating device to obtain a functional aggregate green body.

[0081] S3. The green functional aggregate is fed into a hydrothermal kettle, and steam is introduced into the kettle for hydrothermal reaction. The temperature of the hydrothermal reaction is 180°C, the hydrothermal time is 8 hours, and the hydrothermal pressure is 1 MPa. After the hydrothermal reaction is completed, the finished functional aggregate is obtained.

[0082] Example 3 An artificial functional aggregate, the preparation method of which is as follows: S1. 60 parts of slag, cementitious material (15 parts of silicate cement), siliceous solid waste (25 parts of stone powder) and curing agent (6 parts) are stirred and mixed to prepare a mixture, wherein the curing agent accounts for 6% of the total mass of the slag, cementitious material and siliceous solid waste.

[0083] The curing agent is prepared by weight, and the raw materials include: 75 parts of dispersant, 30 parts of activator, 15 parts of enhancer, 15 parts of activator, 3 parts of promoter, and 13.5 parts of polymerizer, wherein the mass ratio of promoter to polymerizer is 1:4.5.

[0084] The dispersant is fly ash with a particle size of 325 meshes; the activator is sodium sulfate; the enhancer is sodium chloride; the active agent is sodium hydroxide; the promoter is tobermorite; and the polymerizer is water glass.

[0085] The curing agent is prepared by the following method: the dispersant, the stimulator, the reinforcing agent, the activating agent, the accelerator and the polymerizing agent are mixed and then ground to an average particle size of less than 0.075 mm.

[0086] S2. The mixed material is granulated using a disc granulating device to obtain a functional aggregate green body.

[0087] S3. The green functional aggregate is sent into a hydrothermal kettle, and steam is introduced into the hydrothermal kettle for hydrothermal reaction. The temperature of the hydrothermal reaction is 190°C, the hydrothermal time is 4 hours, and the hydrothermal pressure is 1.2 MPa. After the hydrothermal reaction is completed, the finished functional aggregate is obtained.

[0088] Example 4 This embodiment is basically the same as Embodiment 2, except that in this embodiment, the slag solidifying agent added accounts for 1% of the total mass of the slag, cementitious materials, and siliceous solid waste.

[0089] Example 5 This embodiment is basically the same as Embodiment 2, except that in this embodiment, the slag solidifying agent added accounts for 10% of the total mass of the slag, cementitious materials, and siliceous solid waste.

[0090] Example 6 This embodiment is basically the same as Embodiment 2, except that: the accelerator in the curing agent is 1.8 parts, and the polymerizer is 3.7 parts. After calculation, the mass ratio of the accelerator to the polymerizer is 1:2.1.

[0091] Example 7 This embodiment is basically the same as Embodiment 2, except that: the accelerator in the curing agent is 0.4 parts, and the polymerizer is 5.1 parts. After calculation, the mass ratio of the accelerator to the polymerizer is 1:12.8.

[0092] Example 8 This embodiment is basically the same as Embodiment 2, except that the dispersant added to the curing agent is stone powder (instead of fly ash).

[0093] Example 9 This embodiment is basically the same as Embodiment 2, except that the activator added to the curing agent is cement clinker (instead of sodium sulfate).

[0094] Example 10 This embodiment is basically the same as Embodiment 2, except that the reinforcing agent added to the curing agent is calcium chloride (instead of sodium chloride).

[0095] Embodiment 11 This embodiment is basically the same as Embodiment 2, except that the active agent added to the curing agent is calcium hydroxide (instead of sodium hydroxide).

[0096] Example 12 This embodiment is basically the same as embodiment 2, except that the accelerator added to the curing agent is calcium silicate hydrate (instead of tobermorite).

[0097] Comparative Example 1 This embodiment is basically the same as embodiment 2, except that in the curing agent, the accelerator used is 5.5 parts and the polymerizer is 0 parts.

[0098] Comparative Example 2 This embodiment is basically the same as embodiment 2, except that in the curing agent, the accelerator used is 0 parts and the polymerization agent is 5.5 parts.

[0099] Test Case The performance of the functional aggregates prepared in Examples 1-12 and Comparative Examples 1-2 was tested, and the cylinder compressive strength and water absorption were measured according to GB / T17431-2010 "Lightweight Aggregates and Test Methods Thereof". The test results are shown in Table 4 below: Table 4 Performance data of functional aggregate products

[0100] From the above experimental results, different proportions of curing agent are used in Examples 1-5. As the amount of curing agent added increases, the cylinder compressive strength of the functional aggregate increases and the water absorption rate decreases. In terms of comprehensive functional aggregate performance, the most suitable ratio of curing agent to mixture in Examples 1-3 is 2%-6%. In Example 4, the curing agent content is the lowest and the effect is the worst. In Example 5, the curing agent content is the highest. Although the cylinder compressive strength and anti-seepage performance of the functional aggregate are still improved, the increase in effectiveness is significantly reduced.

[0101] From the data in Examples 2, 6-7, with the change of the proportion of the polymerizer in the slag solidifying agent, the cylinder compressive strength of the functional aggregate first increases and then decreases, and the water absorption first decreases and then increases. This is because the polymerizer can effectively improve the functional aggregate molding effect as a binder in the "functional aggregate sphering" stage, and can make the functional aggregate obtained by granulation more "round" while effectively improving the strength of the initial blank after granulation. The low polymerizer is not conducive to the sphering of the functional aggregate; the high polymerizer system is too cohesive as a whole, the molding effect is not good, and the initial blank is easy to adhere and affect the final product. On the other hand, water glass can be hydrated to form silicate minerals inside the mixture, which can effectively promote the hydration of the cementitious material. It has been found through relevant experiments that the polymerizer can be combined with the promoter to form tobermorite seeds inside the system. At the same time, the silicate minerals formed by the hydration of the polymerizer can be used as precursors for the generation of tobermorite, which effectively improves the hydrothermal degree of the product and accelerates the generation of hydrothermal products. A ratio of accelerator to polymerizer that is too low or too high is not conducive to the molding of the product, and affects the degree of hydrothermal reaction at the back end, resulting in a decrease in the cylinder compressive strength of the functional aggregate and an increase in the water absorption rate.

[0102] From the data in Examples 2 and 8, it can be seen that with the change of the dispersant in the slag solidifying agent, the cylinder compressive strength of the functional aggregate decreases and the water absorption rate increases; this may be because although the stone powder has the advantages of high active silica and easy dispersion, its water absorption and dispersion effect is poor, and the 325 mesh fly ash added in Example 2 has not only excellent siliceous activity, but also good adsorption properties, which can effectively absorb the moisture inside the slag, making the slag solidifying agent more accurately and evenly dispersed in actual applications, which is conducive to the solidifying agent to further exert its effect, thereby improving the performance of the functional aggregate.

[0103] From the data in Examples 2 and 9, it can be seen that with the change of the activator in the slag solidifier, the cylinder compressive strength of the functional aggregate decreases and the water absorption rate increases; this may be due to the use of cement clinker in Example 9. The role of cement clinker as an activator is mainly to improve the initial strength of the product. The improvement in the initial strength of the functional aggregate is more obvious, but the stimulation for subsequent strength is relatively low; while the use of sodium sulfate can improve the initial strength of the product, its metal ion sodium ion can form caustic soda under alkaline conditions, effectively improving the alkalinity of the system to accelerate the hydrothermal reaction, increase the degree of hydrothermal reaction, and thus optimize the performance of the functional aggregate.

[0104] From the data in Examples 2 and 10, with the change of the reinforcing agent in the slag solidifying agent, the cylinder compressive strength of the functional aggregate decreases and the water absorption rate increases; it may be due to the fact that when sodium chloride is used as a reinforcing agent, its chloride ions can react with tricalcium silicate in the cementitious material to generate hydrated aluminate, reduce the concentration of calcium hydroxide in the system, accelerate the hydration of tricalcium silicate, and the aluminate generated at the same time can increase the product volume, form an initial skeleton, and be conducive to the further generation of hydrothermal products, while the sodium ions formed by its hydrolysis can be combined with internal hydroxyls, improve the system alkalinity, and accelerate the effect of the rear-end hydrothermal reaction. While calcium chloride is used as a reinforcing agent, its chloride ions can form aluminates, but the increase of calcium ions is easy to conflict with activators, cementitious materials, etc., and the generation of minerals such as calcium sulfate reduces the system alkalinity, which is not conducive to the rear-end hydrothermal reaction, so the cylinder compressive strength and water absorption rate of the obtained functional aggregate decrease.

[0105] From the data in Examples 2 and 11, with the change of the active agent in the slag solidifier, the cylinder compressive strength of the functional aggregate decreases and the water absorption rate increases; this may be because the active agent is calcium hydroxide, which has a lower alkalinity than sodium hydroxide and has a poor stimulating effect. While the alkalinity of sodium hydroxide is higher, its metal ions can penetrate into the slag to cooperate with the activator and enhancer to effectively achieve further modification and dispersion of the microstructure of the clay component, so that the cylinder compressive strength of the functional aggregate increases and the water absorption rate decreases.

[0106] From the data in Examples 2 and 12, it can be seen that with the change of the promoter in the slag solidifying agent, the cylinder compressive strength of the functional aggregate decreases and the water absorption rate increases; this may be because the promoter uses hydrated calcium silicate, which, as the initial hydration product, can form initial crystal seeds, accelerate the hydration reaction process of the cementitious material, and effectively improve the strength of the product, but as an intermediate product, it will further hydrate to form tobermorite as the hydrothermal reaction proceeds; the promoter directly uses tobermorite, which can be directly used as a crystal seed to make the crystals formed by the hydrothermal reaction grow on its promoter, and the dispersed promoter can achieve uniform distribution and efficient synthesis of the product, thereby significantly improving the performance of the functional aggregate, increasing the cylinder compressive strength of the functional aggregate and reducing the water absorption rate.

[0107] Compared with Example 2, the cylinder pressure strength of the functional aggregate in Comparative Examples 1-2 decreases and the water absorption rate increases. When the polymerization agent is lacking, the balling speed of the functional aggregate slows down, the bonding effect between the components deteriorates, and the promoter cannot be used to generate tobermorite seeds or seed attachment points in the system; and the lack of promoter is not conducive to the full progress of the hydration reaction, so the cylinder pressure strength and impermeability of the functional aggregate are seriously deteriorated. It can be seen that the lack of any one of the polymerization agent and the promoter cannot play a synergistic role in the hydrothermal reaction, which is not conducive to the improvement of the performance of the functional aggregate.

[0108] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, change of structural morphology, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0109] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0110] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0111] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

[0112] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A curing agent for artificial functional aggregate, characterized in that: By weight, it comprises: 20-80 parts of dispersant, 5-40 parts of activator, 5-40 parts of enhancer, 1-30 parts of active agent, 1-5 parts of promoter, and 1-20 parts of polymerizer; the weight ratio of the promoter to the polymerizer is 1:2-20; The accelerator is selected from at least one of calcium carbonate, tobermorite, and hydrated calcium silicate; The polymerizing agent is selected from at least one of polyvinyl alcohol, water glass, epoxy resin and organic silica gel binder.

2. The artificial functional aggregate curing agent according to claim 1, characterized in that: The weight ratio of the accelerator to the polymerization agent is 1:4-10.

3. The artificial functional aggregate curing agent according to claim 1, characterized in that: By weight, it comprises: 25-75 parts of dispersant, 10-30 parts of activator, 5-15 parts of enhancer, 5-15 parts of active agent, 0.5-3 parts of promoter and 5-14 parts of polymerizer.

4. The artificial functional aggregate curing agent according to claim 1, characterized in that: The dispersant is selected from at least one of fly ash, stone powder, kiln dust, slag, concrete powder and waste lime; The activator is selected from at least one of cement clinker, sodium sulfate, calcium sulfate and potassium sulfate; The enhancer is selected from at least one of sodium chloride, calcium chloride and potassium chloride; The active agent is selected from at least one of calcium hydroxide, sodium hydroxide, potassium hydroxide and calcium oxide.

5. The artificial functional aggregate curing agent according to claim 1, characterized in that: The dispersant is selected from at least one of fly ash and waste lime; The particle size of the fly ash is 100-600 mesh; The accelerator is at least one of tobermorite and hydrated calcium silicate; The polymerizing agent is at least one of water glass and polyvinyl alcohol.

6. The artificial functional aggregate curing agent according to claim 1, characterized in that: The preparation method of the curing agent is as follows: after mixing the dispersant, the stimulator, the reinforcing agent, the activating agent, the accelerator and the polymerizing agent, the mixture is ground to a particle size of ≤0.075 mm.

7. An artificial functional aggregate, characterized in that: The invention comprises 55-70% of slag, 20-40% of siliceous solid waste, 10-25% of cementitious material and the curing agent according to any one of claims 1 to 6; The curing agent accounts for 1-10% of the total weight of the slag, siliceous solid waste and gelling material.

8. The artificial functional aggregate according to claim 7, characterized in that: The curing agent accounts for 2-6% of the total weight of the slag, siliceous solid waste and cementitious material; The slag is selected from one or more of engineering slag, building slag, shield slag, underground slag, and sawdust; The cementitious material is selected from one or more of silicate cement, slag cement, carbide slag, quicklime, gypsum, and waste lime; The siliceous solid waste is selected from one or more of fly ash, quartz tailings, stone powder, and concrete powder.

9. A method for preparing an artificial functional aggregate, characterized in that: The following steps are involved: S1. Mixing slag, cementitious materials, siliceous solid waste and the curing agent according to any one of claims 1 to 6 to obtain a mixture; S2, the mixture is granulated using a granulating device to obtain a functional aggregate green body; S3. The functional aggregate green body is subjected to hydrothermal reaction to obtain artificial functional aggregate.

10. The method for preparing artificial functional aggregate according to claim 9, characterized in that: In step S2, the granulation equipment is a roller granulation equipment, a disc granulation equipment or an extrusion granulation equipment; In step S3, the hydrothermal temperature of the hydrothermal reaction is 150-200° C., the hydrothermal pressure is 0.48-1.6 MPa, and the hydrothermal time is 4-12 h.

Citation Information

Patent Citations

  • A non-fired ceramsite and its preparation method

    CN113860843B

  • Building silt soil non-sintered ceramic aggregate and preparation method thereof

    CN102617107A

  • Rail shield muck unburned and non-autoclaved ceramsite and preparation method thereof

    CN104710156A

  • Light high-strength silicate ceramsite concrete

    CN111003991A

  • Concrete residual waste treatment process

    CN111116087A